Anthrax toxin receptor 1/tumor endothelial marker 8 promotes gastric cancer progression through activation of the PI3K/AKT/mTOR signaling pathway. Issue 4 (19th February 2020) - Cai, Chen; Dang, Wei; Liu, Shilei; Huang, Ling; Li, Yang; Li, Guoqiang; Yan, Siyuan; Jiang, Chengkai; Song, Xiaoling; Hu, Yunping; Gu, Jun
Abstract: Anthrax toxin receptor 1 (ANTXR1), a type I transmembrane protein, is one of the receptors that facilitates the entrance of anthrax toxin into cells. Previous studies have confirmed the pivotal role of ANTXR1 in progression and tumorigenesis of diverse cancer types. However, the biological function of ANTXR1 in gastric cancer (GC) is still unknown. The present study aimed to investigate the role of ANTXR1 in GC and illuminate the potential molecular mechanisms. Bioinformatics analysis found that ANTXR1 expression was significantly upregulated in GC tissue and its overexpression was associated with poor prognosis of GC patients. Moreover, we confirmed the upregulation of ANTXR1 in GC cell lines and GC tissue by quantitative PCR, western blot analysis, and immunohistochemical analysis. Additionally, high protein expression level of ANTXR1 was positively associated with several clinicopathological parameters in GC patients. In our study, a series of in vitro and in vivo assays were undertaken through strategies of loss/gain‐of‐function and rescue assays. Consequently, our results indicated that ANTXR1 induced proliferation, cell cycle progression, invasion and migration, and tumorigenicity and induced suppressed apoptosis in GC. Mechanistic investigation indicated that ANTXR1 exerted its promoting effects on GC through activation of the PI3K/AKT/mTOR signaling pathway. In conclusion, our findings suggested that ANTXR1 plays a crucial role in the development and progression of GC and could serve as a novel prognostic biomarker and potential therapeutic target for GC. Abstract : The authors observed that anthrax toxin receptor 1 (ANTXR1) expression was significantly upregulated in gastric cancer (GC) tissue and its overexpression was associated with poor prognosis of GC patients. A series of in vitro and in vivo assays were carried out through strategies of loss‐ or gain‐of‐function and rescue assays to find that ANTXR1 promotes gastric cancer progression through activation of the PI3K/AKT/mTOR signaling pathway.